The problem: its importance within educational management (Revista Electrónica Calidad en la Educación Superior, 2022)
The essay presents the problem as an object of study due to its incidence within organizations. However, to treat it, it needs to be understood, which entails a whole approach that aims to clarify a situation. Reason for which it seeks to demonstrate that the analysis of the problem generates enough information to design improvement actions, this, using the problem-based strategy as a method. It is concluded that educational management uses scientific knowledge to know in depth the problems, as well as to clarify the process that must be carried out towards the construction of their solutions; therefore, achieve improvement in institutional functioning.
Keywords: Problem; investigation; decision making; objective educational; strategies